Lenovo Acquires IBM’s x86 Low-end Server Business - Singh, Netra Pal (Industrija, 2015)
This paper presents an analysis of the key events, impacts and issues of Lenovo buying IBM’s x86 low-end server business. The analysis include (i) approval of the deal by regulatory bodies in the United States, Canada, India and China, (ii) security concerns of US government departments, (iii) pricing of the deals, (iv) possible impact on IBM in future, and (v) possibilities of Lenovo making it repeat of acquiring ThinkPad business of IBM. The paper presents analysis of qualitative and time series quantitative data. The qualitative data are mainly consists of different events before and after the acquisition of x86 server IBM business by Lenovo. The quantitative data are analyzed with respect to growth parameters of overall server business and Lenovo server business. Research paper also attempts to find out answer to specific 9 research questions with respect to impact on eco-systems of IBM and Lenovo technologies. Based on analysis, it is inferred that IBM is not able to manage its traditional & well accepted products business in the face of fierce competition & low demand but Lenovo will manage. It was a financial necessity for IBM and strategic expansion in to new markets strategy for Lenovo.